Distribution of water masses and meltwater on the continental shelf near the Totten and Moscow University ice shelves. Issue 3 (16th March 2017) - Silvano, Alessandro; Rintoul, Stephen R.; Peña‐Molino, Beatriz; Williams, Guy D.
Abstract: Warm waters flood the continental shelf of the Amundsen and Bellingshausen seas in West Antarctica, driving rapid basal melt of ice shelves. In contrast, waters on the continental shelf in East Antarctica are cooler and ice shelves experience relatively low rates of basal melt. An exception is provided by the Totten and Moscow University ice shelves on the Sabrina Coast, where satellite‐derived basal melt rates are comparable to West Antarctica. Recent oceanographic observations have revealed that relatively warm (∼−0.4°C) modified Circumpolar Deep Water (mCDW) enters the cavity beneath the Totten Ice Shelf through a 1100 m deep trough, delivering sufficient heat to drive rapid basal melt. Here we use observations from a recent summer survey to show that mCDW is widespread on the continental shelf of the Sabrina Coast, forming a warm (up to 0.3°C) and saline (34.5–34.6) bottom layer overlaid by cold (∼freezing point) and fresh (salinity ∼34.3) Winter Water. Dense Shelf Water is not observed. A 1000 deep m trough allows water at −1.3°C to reach the Moscow University ice‐shelf cavity to drive basal melt. Freshening by addition of glacial meltwater is widespread on the southern shelf at depths above 300–400 m, with maximum meltwater concentrations up to 4–5 ml L −1 observed in outflows from the ice‐shelf cavities. Our observations indicate that the ocean properties on the Sabrina Coast more resemble those found on the continental shelf of the Amundsen and Bellingshausen seas than those typical of East Antarctica. Plain Language Summary: The Totten Glacier drains more ice from the East Antarctic Ice Sheet than any other glacier. The Totten holds a volume of ice equivalent to more than 3.5m of global sea level rise, so changes in the glacier could have significant consequences. East Antarctic ice shelves, including the Totten, were thought to be largely isolated from warm ocean waters and therefore stable. An Australian voyage in 2015 obtained the first oceanographic data near the Totten and Moscow University Ice Shelves. The measurements show that relatively warm water spreads from the open ocean across the continental shelf to reach the ice shelf cavities, where it drives melt of the underside of the ice shelves. The presence of warm water near the ice shelves helps explain rapid rates of melt inferred from satellite data. The study shows that this part of the East Antarctic Ice Sheet is more exposed to warm ocean waters, and therefore may make a larger contribution to sea level rise, than previously thought. Key Points: Warm (up to 0.3°C) modified Circumpolar Deep Water is widespread on the continental shelf, overlaid by fresh Winter Water A series of deep troughs allows relatively warm water to reach the ice‐shelf cavities and drive basal melt Freshening by addition of glacial meltwater is extensive on the inner shelf at depths above 300–400 m